Deoxyribonucleic Acid-dependent Ribonucleic Acid Polymerase Activity in Cells Infected with Influenza Virus - Borland, R. (1968)
Deoxyribonucleic acid (DNA)-dependent ribonucleic acid (RNA) polymerase activity was assayed on nuclear preparations of chick embryo fibroblast cells at various times after infection with an influenza A virus (fowl plague virus) and was compared with the activity of uninfected cells. Polymerase activity was increased by about 60% by 2 hr after infection, and this increase coincided with an increase in RNA synthesis in infected cells, as determined by pulse-labeling with uridine. No difference could be detected between the polymerases of infected and uninfected cells as to their requirements for DNA primer, divalent cations, and nucleoside triphosphates, and they were equally sensitive to addition of actinomycin D to the reaction mixture. It is possible that host cell DNA-dependent RNA polymerase is involved in the replication of influenza virus RNA.